Estudo dos ramos sacrais da aorta abdominal do coelho (Oryctolagus cuniculus) - Daólio, Milena [UNESP]; De Marchi, Paula Nassar [UNESP]; Silva, José Ricardo de Carvalho Pinto e [UNESP]; Guazzelli Filho, Joffre [UNESP]; Schimming, Bruno Cesar [UNESP]; Matheus, Selma Maria Michelin [UNESP]; Filadelpho, André Luiz (My University, 2011)
The objective of this study was to describe the rabit abdominal aorta anatomy, emphasizing the common iliac, external iliac, internal iliac and median sacral arteries. It was used 10 animals from Unesp/Botucatu biotery. The animals injected with Neoprene látex were dissecated and examined. The abdominal aorta emits rami constituting the right and left common iliac arteries which,at bifurcating, originate the external and internal iliac arteries. In 100% of cases, the median sacral artery presents caudally like the abdominal aorta continuation and previous to its bifurcation, always with small caliber, maintaining a slight curvature.

O objetivo deste estudo foi descrever a anatomia da aorta abdominal do coelho enfatizando as artérias ilíacas comuns, artérias ilíacas externas e internas e a artéria sacral mediana. Utilizamos 10 animais do biotério da Unesp/Botucatu. Os animais injetados com Neoprene látex foram dissecados e examinados. A aorta abdominal emite ramos constituindo as artérias ilíacas comuns direita e esquerda que se bifurcam e originam as artérias ilíacas externas e internas. Com relação a artéria sacral mediana em 100% dos casos se apresenta caudal como continuação da aorta abdominal e antes de sua bifurcação e sempre com calibre menor mantém sempre uma ligeira curvatura.
Keywords: Anatomy; Rabbit; Aorta; Anatomia; Coelho; Aorta